Multicomponent Synthesis of Pentyl-Sulfonyl Amidines via Diazoalkane - Contini, Alessandro; Erba, Emanuela; Pellegrino, Sara (Synlett, 2012)
A series of pentyl-sulfonyl amidines was obtained using a multicomponent synthesis process. The rearrangement of unstable tosylazide–cyclopentanonenamine cycloadducts yielded a diazoalkane intermediate. This primary, unstable reaction product showed good reactivity with certain acid compounds in order to form the corresponding derivatives.
Keywords: sulfonyl amidines; multicomponent reaction; diazoalkane; amino acids; antiresorptive agent